Language Attitudes toward English Loanwords in Youth Digital Communication and Their Impact on Academic Achievement - Lukas Schneider (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2010)
The expansion of digital communication among youth has intensified the use of English loanwords in multilingual societies. In Ethiopia, where Amharic dominates daily communication while English functions as the primary language of education, digital interaction increasingly blends local languages with English vocabulary. This study explores Ethiopian youths’ attitudes toward English loanwords in digital communication and examines their potential relationship with academic achievement. A quantitative survey was conducted among 410 high school and university students aged 16–24 in urban Ethiopia. Data were collected using a Likert-scale questionnaire measuring language attitudes, frequency of loanword usage, and self-reported academic performance indicators. Exploratory factor analysis identified underlying attitudinal constructs, while correlation and regression analyses examined relationships between attitudes, language behavior, and academic outcomes. Results show predominantly positive attitudes toward English loanwords (75.9%), particularly regarding their association with modern identity, global connectivity, and communicative efficiency. Three main attitudinal factors emerged: Prestige, Integration, and Purism. Loanword usage was highest in informal digital contexts such as messaging and social media but significantly lower in academic writing. Statistical analyses indicate minimal direct correlation between attitudes toward loanwords and academic performance, suggesting that digital linguistic practices do not necessarily hinder academic proficiency. English loanwords function primarily as pragmatic linguistic resources in youth digital discourse rather than indicators of declining academic language competence. Educational institutions should incorporate digital literacy and sociolinguistic awareness into language education to help students differentiate between informal and academic language registers.